2002
DOI: 10.1097/00042728-200203000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Healing in Chronic Venous Ulcers Treated with Cryopreserved Human Epidermal Cultures

Abstract: background. Cryopreserved epidermal cultures (CEC) offer an "off the shelf" treatment for chronic wounds. These cultures are derived from neonatal foreskin and grow rapidly in vitro to form epidermal sheets. They do not require a biopsy from the patient, an advantage compared to autografts. They seem to act as a biological dressing, stimulating epithelialization from the wound edges and adnexae, probably through growth factor release. objective. To summarize our recent experience with the use of CEC in chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Several studies by other authors have also shown that wound size and wound age are good prognostic markers 5,14–17 . These studies reported risk factors for not healing and, as a result, these models are not strictly prognostic models 31 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies by other authors have also shown that wound size and wound age are good prognostic markers 5,14–17 . These studies reported risk factors for not healing and, as a result, these models are not strictly prognostic models 31 .…”
Section: Discussionmentioning
confidence: 98%
“…The discriminative ability of these models as assessed by the area under the receiver operator characteristic (AROC) curve was excellent (> 0.80). Although not published as truly part of prognostic models, several other authors have also found these parameters to be important for estimating the prognosis of a venous leg ulcer 5,14–17 …”
mentioning
confidence: 99%
See 1 more Smart Citation